2009
DOI: 10.1080/01421590802638048
|View full text |Cite
|
Sign up to set email alerts
|

Influence of educational programs on attitudes of medical students towards psychiatry: Effects of psychiatric experience, gender, and personality dimensions

Abstract: Background: Attitudes of medical students form the basis for medical actions. Because of the specific characteristics of psychiatric patients, positive attitudes of medical students towards psychiatry should be a higher goal in medical education. Aim: We hypothesize that medical students in different educational programs develop different attitudes towards psychiatry. Methods: In a cross-sectional study, students enrolled in different educational programs completed the 'attitudes towards psychiatry' questionna… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

8
40
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(49 citation statements)
references
References 32 publications
8
40
0
1
Order By: Relevance
“…Negative stereotyping and prejudices toward people with mental health issues reduce the likelihood of health workers building rapport with these patients or providing appropriate emotional support. 18 It has been shown that education about mental health issues improves the attitudes of care providers toward people presenting with mental health conditions. [18][19][20] This study aimed to collect cross-sectional data on the self-reported attitudes of physiotherapists working in Western Australia toward psychiatry and their evaluation of their undergraduate education in psychiatry and mental health.…”
mentioning
confidence: 99%
“…Negative stereotyping and prejudices toward people with mental health issues reduce the likelihood of health workers building rapport with these patients or providing appropriate emotional support. 18 It has been shown that education about mental health issues improves the attitudes of care providers toward people presenting with mental health conditions. [18][19][20] This study aimed to collect cross-sectional data on the self-reported attitudes of physiotherapists working in Western Australia toward psychiatry and their evaluation of their undergraduate education in psychiatry and mental health.…”
mentioning
confidence: 99%
“…In studies by Kuhnigk et al, [11,13] response rates of 86%, 88% and 93% were obtained where the 'attitudes towards psychiatry' questionnaire (ATP-30) was administered. In a study by Dixon et al [14] on medical students' attitudes to psychiatric …”
Section: Discussionmentioning
confidence: 99%
“…The significantly higher exposure to confidentiality and informed consent reported by females in our study could possibly be explained by other studies that found that females had a significantly more positive attitude towards psychiatry than their male colleagues. [11,13] This inclination may have contributed to them paying more attention to issues related to confidentiality and informed consent. The significantly higher ethics exposure score for 5th-year students could, among other things, be ascribed to the fact that the junior students are exposed to these issues for the first time and may be more consciously sensitised towards ethical behaviour.…”
Section: Articlementioning
confidence: 99%
See 2 more Smart Citations